Development and Testing of an Experimental Tool to Support Evaluation of Performance in Handling Competing Attentional Demands. (December 2020) - Sebok, Angelia; Adler, Noah; Lofgren, Elijah; McCord, Jake; Spahr, Kimberly; Wickens, Christopher; Clegg, Benjamin
This paper describes the design and evaluation of experimenter capabilities associated with a software tool to train attentional management. This training tool will be used by sensor operators of unmanned aerial systems (UAS), to learn attentional skills associated with managing the competing demands of UAS operational tasks. Before the tool is taken into use, the effectiveness of three different approaches to training will be evaluated in a human-in-the-loop experiment. An agile software development process was used to create, test, and refine this tool. Designing to support experimental evaluations differs in some respects from designing for use by an operational community. Although the overall process is similar, specific needs related to data collection and configurability differ significantly. This paper describes the process, tool, and lessons learned to apply to future experimental systems.